Pengaruh Tehnik Distraksi Auditori Terhadap Tingkat Kecemasan Klien Preoperasi Appendisitis - Sutinah Sutinah (HB PRESS, 2019)
Anxiety is a symptom of unclear concerns, this is related to feelings of uncertainty and helplessness. One therapy for reducing anxiety levels is distraction techniques by listening to music (classical). The classical music has shown the lowest effect on the heart so it can reduce anxiety levels. Clients who has appendic’s surgery, often there is an increase in blood pressure, pulse and body temperature as many as 36 clients who are always changing due to anxiety causing a delay in the operation that will be undertaken. This study was conducted to determine the effect of audiotory distraction techniques on the level of anxiety of preoperative appendixitis clients. This research is a quantitative research with a quasi experimental design, one group pre-post test design. This research was conducted in Raden Mattaher General Hospital Jambi, the sample in this study were clients who would undergo appendic surgery as many as 20 people with accidental sampling technique. The data collection tool uses a questionnaire. The data was processed and analyzed by the dependent T statistical test. The results of statistical tests showed that the average level of anxiety before (pre) was 2.60 and the average level of anxiety after (post) 1.60 with p-value 0.000, meaning that the audiotype distraction technique affected the decrease in anxiety level of preoperative appendixitis clients